Elisabeth Arweck and William Keenan (eds.), Materializing Religion: Expression, Performance & Ritual. - John Hilary Martin, O. P. (Journal for the academic study of religion, 2008)
Elisabeth Arweck and William Keenan (eds.), Materializing Religion: Expression, Performance & Ritual. Ashgate, Aldershot, 2006, pp. 242. ISBN 0754650944.